PENGARUH KEJELASAN ANGGARAN, PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN PENGAWASAN FUNGSIONAL TERHADAP AKUNTABILITAS KINERJA PEMERINTAH (Studi Kasus Pada SKPD di Kabupaten Barito Utara) - Steffani Imelda Lailarawati Lahur; Lamria Simamora; Muhammad Ichsan Diarsyad (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
This study aims to analyze the effect of budget clarity, application of government accounting standards, and functional oversight of government performance accountability in North Barito Regency. The method used in this study is a statistical analysis method whose calculations are carried out using SPSS. This research was conducted on SKPD in North Barito Regency, totaling 84 respondents. The statistical tests used were descriptive statistical analysis, Multiple Linear Regression Analysis, simultaneous test (statistical F test), partial test (statistical t test), and determination test (R2). The results of this study based on a partial test (statistical t test) showed that budget clarity and functional supervision had a significant effect on government performance accountability, while the application of government accounting standards had no significant effect on government performance accountability. Based on the simultaneous test shows that the variables of Budgetary Clarity, SAP Implementation and Functional supervision together have a significant effect on the accountability of government performance at SKPD in North Barito Regency.